Contribution à la faunistique du coralligène. VII. À propos de quelques annélides polychètes rares ou nouvelles (Chrysopetalidae, Syllidae et Spionidae). - Laubier, L. (Annales de l'Institut Océanographique, Paris, Nouvelle Série, 1968)
In this paper, the author decribes some rare or new species of polychaetous Annelids from mediterranean « fonds coralligènes ». Contrarily to the present state of knowledge, Chrysopetalum caecum Langerhans is a valid species. Amongst the Syllidae, some data are given for Haplosyllis depressa chamaeleon Laubier, Ehlersia ferrugina Langerhans and Opisthodonta morena Langerhans. Poorly known species such as Xenosyllis scabra (Ehlers) and Eurysyllis tuberculata Ehlers are fully redescribed. Two species are new to science : Paratyposyllis peresi sp. n. (Syllidae) and Prionospio banyulensis sp. n. (Spionidae).
Kristian Fauchald's Polychaeta DB